2021
DOI: 10.1177/0030727021990032
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of improved cassava varieties in Nigeria: Insights from DNA fingerprinting versus self-reporting varietal identification approaches

Abstract: Much of the empirical studies on crop varietal adoption in Sub-Saharan Africa relied on self-reported adoption in farm-household surveys, which is prone to measurement errors. In addition, farmers’ perceptions of consumption-related varietal traits in adoption studies has received limited attention compared with production-related traits. Using DNA-based and self-reported adoption measures, we analyze the adoption of improved cassava varieties (ICVs) with a focus on the extent of varietal misidentification, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Most studies on the CVC focus on the production node, with only a few studies considering activities at the processing and market nodes of the chain. At the production node, studies address issues related to adoption of improved cassava varieties (Opata et al. , 2021; Afolami et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most studies on the CVC focus on the production node, with only a few studies considering activities at the processing and market nodes of the chain. At the production node, studies address issues related to adoption of improved cassava varieties (Opata et al. , 2021; Afolami et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2022) found that smallholder farmers in Ghana showed strong preferences for cropping systems that provide positive nutritional gain. Our finding also lends credence to the growing R&D interventions geared toward improving farmers' dietary protein via sorghum–legume intercropping (Sauer et al ., 2018), and toward addressing deficiencies of micronutrients such as vitamins, zinc and iron via biofortification of sorghum (Shikuku et al ., 2019; Opata et al ., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, only seven out of ten farmers classified their varieties correctly. The reviewed studies report that 34 percent of cassava farmers (on aggregate), 28 percent of maize farmers, and 19 percent of rice farmers misclassified the variety grown on their farms (Floro et al, 2018; Kretzschmar et al, 2018; Trinade, 2019; Wossen et al, 2019a; Opata et al, 2021). The dichotomy of improved versus local variety allows disaggregating the false identifications into false positives (FP, i.e., a local variety is labeled as improved) and false negatives (FN, i.e., an improved variety is labeled as local).…”
Section: Literature Search Methodologymentioning
confidence: 99%
“…Nevertheless, the validity of these assessments is critically dependent on farmer identification and recall of crop varieties. There exists a plethora of evidence in the literature for the misidentification of varieties by farmers and subject experts (Opata et al, 2021).…”
Section: Introductionmentioning
confidence: 99%